THE USE OF QUESTION ANSWER-RELATIONSHIP (QAR) STRATEGY ON IMPROVING STUDENTS’ READING COMPREHENSION AT SMAN 1 JATITUJUH - Rully Khoeru Solihin; Muaz Muaz (Journal of English Language Learning, 2022)
Abstract. The objectives of this research are to find out whether or not there is a significant of difference between the Reading Comprehension of the Twelfth Grade Students of SMAN 1 Jatitujuh taught before and after using the Question-Answer Relationship (QAR) strategy. The method in this study was quantitative. The subject of this research is students in XII MIPA 1. The research instrument used by the writer is a test (pre-test and post-test) The result of this research, it was found that of the reading comprehension of the twelfth-grade students of SMAN 1 Jatitujuh before being taught by using QAR strategy was sufficient, the mean is 69.71. Meanwhile of the reading comprehension of the twelfth grade students of SMAN 1 Jatitujuh after being taught by QAR strategy was categorized good, the mean is 85. Moreover, the calculation of the t-count, the score is 11.867 was higher than t-table, score is 2.032 (11.867 > 2.032) in level significance 5%. Based on the result above, it could be concluded that Question Answer Relationship (QAR) strategy could improve reading comprehension of the twelfth grade students of SMAN 1 Jatitujuh. In addition, the subjects also responded positively the implementation of QAR strategy.